«Que dorénavant chacun fuie paillardise, oisiveté, gourmandise...» Réforme et contrôle des moeurs la justice consistoriale dans le Pays de Neuchâtel (1547-1848) - Robert, Michèle (Editions Alphil Presses universitaires suisses, 2016)
Neuchâtel adopted the Reformation in 1530. What impact did this decision by the citizens of the city have on the population? This book describes the disci-pline that has since surrounded the parishioners of the canton of Neuchâtel and the lordship of Valangin and evoked three centuries of Neuchâtel consis-tories. Based on the analysis of thousands of cases, it draws back the cur-tain on daily life, love, the revolts of a small population, mostly rural, in which the sources speak only rarely.